تعلم الصرف العربي عبر الوسائط المتعددة - Md. Noor, Mohamad Lukman Al Hakim; Sahrir, Muhammad Sabri (IIUM PRESS, 2017)
This book deals with the issue of learning Arabic morphology by using multimedia via the World Wide Web as it seeks to help students to learn through the design of a computer-assisted programme. Among the factors related to this study include the difficulties faced by many non-native Arabic language learners in learning Arab morphology, including a large number of morphological terms that lead to student psychological disorder and distraction of mind. It becomes worse if they are presented with the different views of scholars, which leads them to avoid the subject of morphology due to its complexity and the difficulty of material based on learners’ perception. This study adopted both descriptive and analytical methodologies. The researcher collected information about the difficulties in learning Arabic morphology and the theories of learning the Arabic language via the World Wide Web, and designed a computer-assisted programme by using multimedia via the URL of http://efolio.iium.edu.my/courses/sorof/index.html through Blendspace’s website. It was developed in light of instructional design model of ADDIE based on the respondents’ views, suggestions and needs. The researcher performed the validity and reliability check of this study among the experts in the field of teaching Arabic as a second language and educational technology. The researcher found that this multimedia learning programme is highly accepted by the respondents, as it leads to a productive and successful process of learning Arabic morphology as a second language.